Developing an integrative customer satisfaction model: an application of customer experience in Malaysian e-banking services - Bashir, Md Abdul; Ali @ Hamid, Mass Hareeza; Akther, Nafiza; Lam, Mun; Mohd Paiz, Nur Ain; Islam, Amirul (Science & Engineering Research Support Society, 2020)
Electronic Banking (e-banking) is referred to e-finance services, provided by the banks in the form of goods or services through electronic delivery systems. The emergence of e-banking since its inception has played a major role in the country’s economic development and boosting customer satisfaction. It has now become one of the pre-requisite guiding the decision of customers in making the decision of choosing a bank to relate with. This is happening because of the general global transformation into the e-world and the consumer awareness of their e-banking requirement and conveniences from a particulars bank as compared to the initial conventional banking system. Taking from the existing literature of customer behavior, on e-banking services, research from different scholars has revealed the effects of demographic characteristics of the customers, such as age, gender, income and level of education etc. on e-banking provision of goods and services. It is on this ground that this study proposes an extension to the study by proposing an Integrative Model of Customer Experience in Malaysia E-Banking Service Delivery. However, from the theoretical discussion of the above review, it was observed that the original model suffers some limitations. As such, this paper deemed it necessary to examine an additional driver influences, perception, and attitude toward E-banking adoption in Malaysia.